2007
DOI: 10.1002/maco.200604038
|View full text |Cite
|
Sign up to set email alerts
|

Effect of turbulent flow on the anodic and cathodic kinetics of API X52 steel corrosion in H2S containing solutions. A rotating cylinder electrode study

Abstract: This work presents the electrochemical kinetics results measured during the corrosion of API X52 pipeline steel immersed in aqueous environments, containing dissolved hydrogen sulfide (H 2 S) under turbulent flow conditions. In order to control the turbulent flow conditions, a rotating cylinder electrode (RCE) was used. Five different rotation rates were studied: 0 (or static conditions), 1000, 3000, 5000 and 7000 rpm. It was found that the turbulent flow increases the corrosion rate and the corrosion mechanis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 26 publications
0
12
0
Order By: Relevance
“…In the eighties, Morris et al used a carbon steel rotating disc electrode to study corrosion in aqueous H 2 S systems of acid pH [15]. They concluded that H 2 S did not modify the cathodic process in the activation region, but they noticed also that H + diffusion control disappeared gradually with H 2 S. Measurements in controlled turbulent flow conditions were reported by Galvan-Martinez et al [16], with a rotating cylinder made of carbon steel. They examined the hypothesis of a direct H 2 S reduction according to Equation (6), but they noticed that the corrosion potential was situated in a region where the cathodic current was under H + mass transfer limitation.…”
Section: Co H O H Hcomentioning
confidence: 97%
“…In the eighties, Morris et al used a carbon steel rotating disc electrode to study corrosion in aqueous H 2 S systems of acid pH [15]. They concluded that H 2 S did not modify the cathodic process in the activation region, but they noticed also that H + diffusion control disappeared gradually with H 2 S. Measurements in controlled turbulent flow conditions were reported by Galvan-Martinez et al [16], with a rotating cylinder made of carbon steel. They examined the hypothesis of a direct H 2 S reduction according to Equation (6), but they noticed that the corrosion potential was situated in a region where the cathodic current was under H + mass transfer limitation.…”
Section: Co H O H Hcomentioning
confidence: 97%
“…On the other hand, studies on H 2 S corrosion were mainly focused on anodic mechanism or on the formation of FeS scale formation [8,[16][17][18][19]. Electrochemical aspects of H 2 S benefited much less investigations, though it was found to have strong impact on the cathodic current density [1,8,20]. Recent electrochemical investigations were thus performed using well controlled hydrodynamic systems and show that H 2 S contribution might not fully be explained by a buffer effect [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…The working electrode was inserted and operated at a speed of 1000 rpm through connection to a Pine Model MSRX electrode rotator. The rotating electrode with speed of 1000 rpm was prepared for simulating turbulent flow conditions related to data obtained in real life system [24][25][26][27]. The electrochemical cell was connected for LP measurement.…”
Section: Linear Polarization (Lp)mentioning
confidence: 99%